2018
DOI: 10.3390/designs2030032
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Electrical Coupling in Solar Cell Thermoelectric Hybridization

Abstract: Abstract:It is well known that the major constraints to the efficiency of photovoltaic devices come from the generation of heat. In this context, thermoelectric generators have been proposed as a viable heat recovery solution, leading to an increase of the overall efficiency. Within this kind of hybrid solution, the photovoltaic and thermoelectric parts can be either electrically separated or connected in the same circuit. In the latter case, the presence of the thermoelectric generator in series to the solar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In addition, Lorenzi et al [80] analysed the effect of several parameters on the power output of an electrical coupled PV/TEG system. Results obtained showed that for solar cells with a small series resistance, the voltage needed for electrical lossless coupling was smaller.…”
Section: Hybrid System Couplingmentioning
confidence: 99%
“…In addition, Lorenzi et al [80] analysed the effect of several parameters on the power output of an electrical coupled PV/TEG system. Results obtained showed that for solar cells with a small series resistance, the voltage needed for electrical lossless coupling was smaller.…”
Section: Hybrid System Couplingmentioning
confidence: 99%
“…[ 10 ] Lorenzi et al further evaluated the match on internal resistance of PV and TEG (electrically connected in series) and their influence on total power output. [ 52 ] However, there's no theoretical or numerical simulation about the d T c and the TEG optimization based on d T c under a given PV device, which should be general for such type of device integration based on various PV techniques.…”
Section: Resultsmentioning
confidence: 99%
“…For the realization of converters combining thermal and solar sources (see Figure 4 a), a laminated structure is proposed in [ 36 , 37 ], where solar and thermoelectric cells are used. This hybridization enabled in this case an improvement of the maximum power output by 47% and 36% in comparison to the single solar cell and thermoelectric cell, respectively.…”
Section: Energy Supply For Wireless Sensor Nodesmentioning
confidence: 99%
“…The resulting system structure is complex and contains several layers to be able to ensure the hybridization. In [ 37 , 38 ], a solution combining thermoelectric and solar cells is developed to power wearable medical devices. In this case, the main purpose of combining both sources is to ensure the continuous reliable energy availability as photovoltaic cells have a good performance limited to outdoors.…”
Section: Energy Supply For Wireless Sensor Nodesmentioning
confidence: 99%